2012
DOI: 10.2355/isijinternational.52.74
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Behavior of δ-ferrite in Continuously Cast Slabs of SUS304 during Heat Treatment

Abstract: The dissolution of δ -ferrite in continuously cast slabs of SUS304 has been studied during heat treatment in the temperature range of 1 373 to 1 473 K. The dissolution behavior can be expressed by KolmogorovJohnson-Mehl-Avrami equation. The dissolution rate is affected by annealing temperature and secondary dendrite arm spacing. Moreover, the numerical methodology for multi-phase field method has been performed in Fe-Cr-Ni alloy. It is thought that dissolution behavior of δ -ferrite during heat treatment can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…To reduce the amount of the delta-ferrite phase in the steels, the steels were heat-treated at 1273 K for 96 h, hot-rolled at 1473 K from 20 mm down to ca. 12 mm in thickness, and finally reheated at 1273 K for 96 h. 20,21 Afterward, the steels were solution-treated at 1323 K for 0.5 h. After heattreatment, the steels were cut into specimens with dimensions of 15 mm × 25 mm × 5 mm. The specimens were ground with a series of SiC papers up to 1500 grit and then polished by a diamond paste down to 1 μm.…”
Section: Methodsmentioning
confidence: 99%
“…To reduce the amount of the delta-ferrite phase in the steels, the steels were heat-treated at 1273 K for 96 h, hot-rolled at 1473 K from 20 mm down to ca. 12 mm in thickness, and finally reheated at 1273 K for 96 h. 20,21 Afterward, the steels were solution-treated at 1323 K for 0.5 h. After heattreatment, the steels were cut into specimens with dimensions of 15 mm × 25 mm × 5 mm. The specimens were ground with a series of SiC papers up to 1500 grit and then polished by a diamond paste down to 1 μm.…”
Section: Methodsmentioning
confidence: 99%
“…The control of the residual ferrite amount in stainless steel castings is of great importance when aiming at a good product quality. Table 10 shows the calculated (SOL), experimental, [22,31,85,97,[133][134][135][136] and predicted [137] residual ferrite amounts in numerous stainless steels. As shown at the bottom of Table 10, the average deviation between the calculations and the experimental measurements is 1.12 pct and that deviation between the calculations and the predictions [137] is 2.40 pct.…”
Section: Residual Ferrite Amounts Of Stainless Steelsmentioning
confidence: 99%
“…In both calculation algorithms for the SDAS as well as the austenite grain size, Table 10. Calculated (SOL), experimental, [22,31,85,97,[133][134][135][136] and predicted [137] residual ferrite amounts in stainless steels. CRT denotes the cooling rate.…”
Section: Microstructure Datamentioning
confidence: 99%
“…It was observed that the DRX would progressively rise as the deformation temperature increased, and an increase in strain rate was identified as result in a significant reduction in both the DRX grain size and DRX fraction. Fukumoto et al [ 19 ] conducted a systematic study on the dissolution behavior of δ ‐ferrite in SUS304 stainless steel during heat treatment. And the results showed that the annealing temperature and secondary dendrite arm spacing influence the dissolution rate.…”
Section: Introductionmentioning
confidence: 99%